Analisis Implementasi Electronic-Cutoms Declaration dari Sudut Pandang Pengguna Jasa - Wibowo, Shabha Amadea; Irshadi, Ardandy Amrie (JURNAL PERSPEKTIF BEA DAN CUKAI, 2024)
This study analyzes public expectations and perceptions of the implementation of the Electronic-Customs Declaration (E-CD) in Indonesia using the eGovQual and Importance Performance Analysis (IPA) approaches. E-CD, gradually implemented since 2022 at various international airports, digitizes the process of declaring passengers' belongings in accordance with Minister of Finance Regulation Number PMK-203/PMK.04/2017. The aim of this research is to identify public sentiment toward E-CD and pinpoint critical areas for improvement to enhance service quality. The research uses a quantitative method, collecting data through questionnaires distributed to 57 respondents who met the study criteria. The results show that the majority of respondents are aware of the obligation to complete the E-CD, with most filling out the form on the day of arrival in Indonesia. IPA analysis reveals that the quick response of customs officers requires special attention, while the reliability and trust in the E-CD service have generally met public expectations. These findings indicate a gap between service expectations and performance, primarily due to non-technological factors such as knowledge and support from officials. Recommendations from this study include improving public communication and refining the E-CD system to support more effective future implementation.